(NpROBLEMY KOSMOHIMII (B/s - (NwOJTKEWI^(B, (NgEORGIJ wITOLXDOWI^s; (NsU^KOW(B, (Na(B.(Na(B.s ((NrOSTOW(B-(NNA(B-(NdONU (B:s (NiZD(B-(NAO rOSTOWSKOGO UN(B-(NTA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 320-329s
(NrOSTOWSKIJ UNIWERSITET IM(B. (Nm(B.(Na(B. (NsUSLOWAs
Keywords: (NkOSMI^ESKAQ HIMIQs